Which of these is greater 2 0 1 7 2 0 1 7 ! or 2 0 1 8 2 0 1 8 ! ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note that f ( x ) = 2 0 1 8 2 0 1 7 ! ⋅ x is a strictly increasing function of x ≥ 0 . Also, if we set G = 2 0 1 7 2 0 1 7 ! , then G 2 0 1 7 = 2 0 1 7 ! and f ( G ) = 2 0 1 8 G 2 0 1 7 ⋅ G = 2 0 1 8 G 2 0 1 8 = G , so it follows that f ( x ) ⎩ ⎨ ⎧ < = > ⎭ ⎬ ⎫ G ⟺ x ⎩ ⎨ ⎧ < = > ⎭ ⎬ ⎫ G or, by setting x = 2 0 1 8 , 2 0 1 8 2 0 1 8 ! ⎩ ⎨ ⎧ < = > ⎭ ⎬ ⎫ 2 0 1 7 2 0 1 7 ! ⟺ 2 0 1 8 ⎩ ⎨ ⎧ < = > ⎭ ⎬ ⎫ 2 0 1 7 2 0 1 7 !
To finish, note that 2 0 1 7 ! is the product of 2 0 1 7 non-negative numbers all less than 2 0 1 8 , so 2 0 1 8 = 2 0 1 7 2 0 1 8 2 0 1 7 > 2 0 1 7 2 0 1 7 ! ⟹ 2 0 1 8 2 0 1 8 ! > 2 0 1 7 2 0 1 7 !
Remark: The first part of my solution actually yields a method to give more inequalities. For instance, using AM-GM, 2 0 1 7 2 0 1 7 ! < 2 1 + 2 0 1 7 = 2 2 0 1 8 ⟹ 2 0 1 8 2 2 0 1 8 ! > 2 0 1 7 2 0 1 7 !
From the pattern- 1<root2!,root2!<cuberoot3!,cuberoot3!<fourth root of4!
Suppose that 2 0 1 8 2 0 1 8 ! = 2 0 1 7 2 0 1 7 ! = x . Then x 2 0 1 8 = 2 0 1 8 ! and x 2 0 1 7 = 2 0 1 7 ! , which means that:
x 2 0 1 7 x 2 0 1 8 = 2 0 1 7 ! 2 0 1 8 ! ⇔ x = 2 0 1 8
But if x = 2 0 1 8 then x 2 0 1 8 = 2 0 1 8 ! and x 2 0 1 7 = 2 0 1 7 ! are both obviously FALSE ( 2 0 1 8 2 0 1 8 = 2 0 1 8 ! = 2 0 1 7 ! ), meaning that 2 0 1 8 2 0 1 8 ! = 2 0 1 7 2 0 1 7 ! .
Next, let's assume that: 2 0 1 8 2 0 1 8 ! < 2 0 1 7 2 0 1 7 ! ⇔ 2 0 1 7 2 0 1 7 ! 2 0 1 8 2 0 1 8 ! < 1
And assign x and y in the following way: y = 2 0 1 8 2 0 1 8 ! ⇔ y 2 0 1 8 = 2 0 1 8 ! x = 2 0 1 7 2 0 1 7 ! ⇔ x 2 0 1 7 = 2 0 1 7 ! Then, our assumption means that: x y < 1 → ( x y ) 2 0 1 8 < 1 ⇔ x ⋅ x 2 0 1 7 y 2 0 1 8 < 1 ⇔ x > 2 0 1 7 ! 2 0 1 8 ! ⇔ x > 2 0 1 8 But if x > 2 0 1 8 then x 2 0 1 7 = 2 0 1 7 ! is (again) obviously FALSE (eg. 2 0 1 9 2 0 1 7 = 2 0 1 7 ! ), meaning that the assumption 2 0 1 8 2 0 1 8 ! < 2 0 1 7 2 0 1 7 ! it's also FALSE.
Therefore 2 0 1 8 2 0 1 8 ! > 2 0 1 7 2 0 1 7 ! .
Problem Loading...
Note Loading...
Set Loading...
We know x ! ≈ 2 π x × ( e x ) x
Therefore, x x ! ≈ ( 2 π x ) 2 x 1 × e x
As x gets arbitrarily large, 2 x 1 goes to 0. If we plug in 2017 and 2018: e 2 0 1 8 − e 2 0 1 7 = e 1
Therefore, 2 0 1 7 2 0 1 7 ! < 2 0 1 8 2 0 1 8 ! by approximately e 1 .